From Classroom to Community: Enhancing Undergraduate Research Through an Interdisciplinary Cohort Model - Fakhoury, Renato; Peterson, Emma (Journal of Interdisciplinary Studies in Education, 2024)
While scholarship in education has found that undergraduate involvement in research is beneficial to both students and mentors, those experiences are still incipient in the social sciences when compared to students in science and technology disciplines. The lack of community-based research programs in the social sciences is glaring, as students do not need to be in laboratories to do work. This paper analyzes how an emphasis on community through cohort models impacts undergraduate student experience in research, taking from the Emerging Scholars Program, an interdisciplinary research program at the University of Massachusetts Lowell where yearly cohorts of undergraduate students are matched with faculty research projects and attend meetings, workshops, and presentations together. We find that the cohort-model has effectively created a robust community that fosters positive relationships between students, mentors, and fellow colleagues. These relationships in turn are crucial in the development of professional skills such as public speaking and also build a layer of emotional support that allows students to collaborate on shared solutions and aim higher in their professional goals. The results from this study offer valuable insights into how universities can ensure that students have a successful, meaningful, and impactful research experience beyond the classroom.